Sexually dimorphic aggression indicates male gray wolves specialize in pack defense against conspecific groups - Cassidy, Kira A.; Mech, L. David; MacNulty, Daniel R.; Stahler, Daniel R.; Smith, Douglas W. (DigitalCommons@University of Nebraska - Lincoln, 2017)
Aggression directed at conspecific groups is common among gregarious, territorial species, and for some species such as gray wolves (Canis lupus) intraspecific strife is the leading cause of natural mortality. Each individual in a group likely has different measures of the costs and benefits associated with a group task, such as an aggressive attack on another group, which can alter motivation and behavior. We observed 292 inter-pack aggressive interactions in Yellowstone National Park between 1 April 1995 and 1 April 2011 (>5300 days of observation) in order to determine the role of both sexes, and the influence of pack, age, and other traits on aggression. We recorded the behaviors and characteristics of all individuals present during the interactions (n = 534 individuals) and which individuals participated in each step (i.e. chase, attack, kill, flight) of the interaction. Overall, all wolves were more likely to chase rivals if they outnumbered their opponent, suggesting packs accurately assess their opponent’s size during encounters and individuals adjust their behavior based on relative pack size. Males were more likely than females to chase rival packs and gray-colored wolves were more aggressive than black-colored wolves. Male wolves and gray-colored wolves also recorded higher cortisol levels than females and black-colored wolves, indicating hormonal support for more intense aggressive behavior. Further, we found a positive correlation between male age and probability of chasing, while age-specific participation for females remained constant. Chasing behavior was influenced by the sex of lone intruders, with males more likely to chase male intruders. This difference in behavior suggests male and female wolves may have different strategies and motivations during inter-pack aggressive interactions related to gray wolf mating systems. A division of labor between pack members concerning resource and territory defense suggests selection for specific traits related to aggression is an adaptive response to ...